Kejadian Kardiovaskular Mayor di Rumah Sakit pada Pasien STEMI di Era Pandemi COVID-19 - Mangkoesoebroto, Arjatya Pramadita; Herry, Yan; Sofia, Sefri Noventi; Bahrudin, Udin (RSUP Dr. Kariadi, 2023)
BACKGROUND: The Coronavirus Disease 2019 (COVID-19) pandemic has become a global burden, changing healthcare system and affecting patients with ST segment elevation myocardial infarction (STEMI). Several countries reported a decrease in hospital admission, changing management, increase total ischemic time, and major cardiovascular events (MACE) in the pandemic era. However, there is limited data especially in Indonesia. OBJECTIVE: To know the differences in admissions, characteristics, management and in-hospital MACE in STEMI patients between pre and pandemic era. METHODS: Comparative observational analytical study was done on 169 patients in the pre-pandemic (12 March 2019-11 March 2020) compared to 163 patients in the pandemic era (12 March 2020-30 September 2021) with STEMI at dr. Kariadi Semarang Hospital. Assessment of monthly admission rates, total ischaemic time, reperfusion management, COVID-19 status and MACE were carried out. RESULTS: During the COVID-19 pandemic, there was a decrease in the average admission of 14.1 to 8.6 patients per month (p<0.001), increase total ischaemic time of 8.78 (3.22-19.68) hours to 10.22 (3 .20-20.43) hours (p<0.001), decreased use of primary PCI (97.0% vs. 83.4%, p<0.001), increased fibrinolytic (1.8% vs8.6%,p=0.010) and no reperfusion (1.2%vs8.0%, p=0.007). There was a significant increase in MACE in the era of the COVID-19 pandemic (10.7%vs22.1%,p=0.008), with mortality (4.7%vs11.7%,p=0.035), stroke (1.2%vs1.8%,p=0.680), cardiogenic shock (4.1%vs11.0%, p=0.030), and acute pulmonary edema (3.6%vs10.4%,p=0.024). CONCLUSION: There was a decrease in admissions and primary PCI procedure, increase use of fibrinolytics and without reperfusion, total ischemic time prolongation, and significant increase of in-hospital MACE in STEMI patients during the COVID-19 pandemic.